Kepemimpinan Kyai dalam Membentuk Keadaban Santri di Pondok Pesantren Nurul Jadid - Hasan, Moch. Zainul; Barizi, Ahmad (IAI Darussalam, 2024)
This study examines Kyai's leadership in shaping Santri civilization in Nurul Jadid Paiton Probolinggo's Residence. The research uses a qualitative case study approach, with data collection methods through observations, interviews, and documentation. The subject of the study is Kh. Moh. Zuhri Zaini, BA, as the nurses of the current nursing house. The results of the research show that Kyai Zuhri's leadership style has successfully achieved some of the desired indicators in shaping a central civilization. It is in line with the vision of the founder and first guardian, Kh. Zaini Mun'im, which was later continued by his son, Kh. Moh. Hasyim Zaini, and was perfected by the third guardian Kh. Abdul Wahid Zaini who formulated the Trilogy and Panca Consciousness Santri based on the book Bidayatul Hidayah by Imam Al-Ghazali. Kyai Zuhri's charismatic leadership and integrity have enabled the ministry and society to implement the good manners as well as the charitable manners presented by Kyai.